Theoretical and Experimental Contributions on the Use of Smart Composite Materials in the Construction of Civil Buildings with Low Energy Consumption - Vasile Bendic; Dan Dobrotă (Energies, 2018)
The paper presents the theoretical and experimental studies undertaken for the realization of an intelligent composite material with phase shift that has optimal characteristics in the thermal energy storage process and an experimental method for integrating the material with phase change in a possible efficient system to be used in the construction of a dwelling. It analyzes the main factors in designing such systems (the temperature limits between which the system must operate, the melting/solidification temperature of the Phase Change Material (PCM), the latent heat of the PCM, the degree of thermal loading, the bed configuration of PCM capsules and a PCM-RB01 material is set. A micro-encapsulation method was chosen and a “solar wall” is made where the incident solar radiation is absorbed by the PCM embedded in the wall, so the stored heat is used for heating and ventilation of a home. Experimental research has shown that developed PCM allows a maximum room temperature reduction of about 4 °C during the day and can reduce the night-time heating load. Also, despite the lower thermal energy absorption capacity, the developed PCM-RB01 material provides a superior physical stability compared to the classical types of integration.